MENTORING IN THE COMMUNITY DEVELOPMENT WORKERS PROGRAMME - Motlhake, Bona Neville (My University, 2011)
Since the advent of democracy in 1994, South African government has continued to build capacity in national, provincial and local spheres of government. The Community Development Workers were brought in as multi-skilled public servants to alleviate the capacity problem of the local government sphere. The purpose of this research was to investigate how effective mentoring, as a component of Community Development Workers programme is, during the learnership and after completion during the initial stages when Community Development Workers go into their workplace. The research uses focus group interviews to look at the mentoring of the Community Development Workers during and after the learnership in the Tshwane and eThekwini Metros. The main findings of the research are that there were no mentors in the Tshwane Metro during and after the learnership. There were mentors in the eThekwini Metro during and after the learnership and they were making a difference in the Community Development Workers programme
MM - P&DM
Keywords: Mentoring; Community programmes; Community development programmes